2018
DOI: 10.1002/jcb.27062
|View full text |Cite
|
Sign up to set email alerts
|

Differential GIP/GLP‐1 intestinal cell distribution in diabetics’ yields distinctive rearrangements depending on Roux‐en‐Y biliopancreatic limb length

Abstract: As incretins are known to play an important role in type 2 diabetics (T2D) improvement observed after Roux-en-Y gastric bypass (RYGB), our aim was to assess whether increasing the length of RYGB biliopancreatic limb in T2D would modify the incretin staining cell density found after the gastric outlet. Small intestine biopsies (n = 38) were harvested during RYGB at two different distances from the duodenal angle; either 60-90 cm (n = 28), from non-diabetic (n = 18) patients, and T2D (n = 10), or 200 cm (n = 10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
7
0
4
Order By: Relevance
“…A statistical analysis of the GIT of segments A and C (p=0.001) was performed, considering the significance level of the nonparametric Kruskal-Wallis test established for the value of p<0.001. There was a significant difference between biopsy results in point C (compared to other groups 120 cm from the EEA), with mean cell count of 12.5 (±4.73) and median of 11.5 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A statistical analysis of the GIT of segments A and C (p=0.001) was performed, considering the significance level of the nonparametric Kruskal-Wallis test established for the value of p<0.001. There was a significant difference between biopsy results in point C (compared to other groups 120 cm from the EEA), with mean cell count of 12.5 (±4.73) and median of 11.5 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies in animal models (rats, pigs, cats, and dogs) showed incretin cells distribution along intestinal segments using polyclonal antibodies to perform qualitative or semi-quantitative assessment of the distribution of immunoreactive cells 16 , 17 , 18 , 19 . However, very few studies using human tissue from a small number of surgical biopsy specimens collected during Roux-en-Y gastric bypass (RYGB) confirmed the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms and their relevance to the improved metabolic profile have been extensively investigated over the past decade. Proposed pathways include normalization of metabolic hormone secretions such as peptide YY (PYY) 26,27 , gastric inhibitory peptide (GIP) 28 and glucagon-like peptide-1 (GLP-1) 29,30 , stimulation of glucose sensing transporters 15 and vagal afferent nerves [31][32][33] , as well as changes in gut microbiome 29,34,35 and bile acid levels 13,34 . The combination of these physiological alterations reduces hunger sensations and enhances tissues' energy expenditure and subsequently improves insulin sensitivity and glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that the methodology used to evaluate pancreatic insulin content consisted in the assessment of the relative density of insulin expressing cells within the pancreatic tissue based on computerized morphometric analysis. This is a very reliable tool since it is observer independent and has been extensively used by our research group 30,31 Besides the modulation of insulin secretion, GLP-1 was demonstrated to stimulate proliferation and inhibit apoptosis on β-cells in rodent models. 27 Thus, despite the acute nature of study, we sought to determine Ki67 expression as a surrogate marker of cell proliferation, which was found to be higher in rats fed with free AA as compared with rats fed with iProtein, suggesting that free AA could have a cellular activation effect on pancreatic islets.…”
Section: Glp-1mentioning
confidence: 99%